Chronic kidney disease: Pathological and functional evaluation with intravoxel incoherent motion diffusion‐weighted imaging. Issue 5 (21st September 2017) - Mao, Wei; Zhou, Jianjun; Zeng, Mengsu; Ding, Yuqin; Qu, Lijie; Chen, Caizhong; Ding, Xiaoqiang; Wang, Yaqiong; Fu, Caixia
Abstract : Background: Because chronic kidney disease (CKD) is a worldwide problem, accurate pathological and functional evaluation is required for planning treatment and follow‐up. Intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) can assess both capillary perfusion and tissue diffusion and may be helpful in evaluating renal function and pathology. Purpose: To evaluate functional and pathological alterations in CKD by applying IVIM‐DWI. Study Type: Prospective study. Subjects: In all, 72 CKD patients who required renal biopsy and 20 healthy volunteers. Field Strength: 1.5T. Assessment: All subjects underwent IVIM‐DWI of the kidneys, and image analysis was performed by two radiologists. The mean values of true diffusion coefficient (D), pseudo diffusion coefficient (D*), and perfusion fraction (f) were acquired from renal parenchyma. Correlation between IVIM‐DWI parameters and estimated glomerular filtration rate (eGFR), as well as pathological damage, were assessed. Statistical Tests: One‐way analysis of variance (ANOVA), paired sample t ‐test and Spearman correlation analysis. Results: The paired sample t ‐test revealed that IVIM‐DWI parameters were significantly lower in medulla than cortex for both patients and controls ( P < 0.01). Regardless of whether eGFR was reduced, ANOVA revealed that f values of renal parenchyma were significantly lower in patients than controls ( P < 0.05). Spearman correlation analysis revealed that there were positive correlations between eGFR and D (cortex, r  = 0.466, P < 0.001; medulla, r  = 0.491, P < 0.001), and between eGFR and f (cortex, r  = 0.713, P < 0.001; medulla, r  = 0.512, P < 0.001). Negative correlations were found between f and glomerular injury (cortex, r  = −0.773, P < 0.001; medulla, r  = −0.629, P < 0.001), and between f and tubulointerstitial lesion (cortex, r  = −0.728, P < 0.001; medulla, r  = −0.547, P < 0.001). Data Conclusion: IVIM‐DWI might be feasible for noninvasive evaluation of renal function and pathology of CKD, especially in detection of renal insufficiency at an early stage. Level of Evidence : 1 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2018;47:1251–1259.